Religious Tourism and Sustainable Economic Development: Examining the Nexus through the Case of Gurdwara Darbar Sahib, Pakistan - Bano, Neelam; Arshad, Zubair; Imtiaz, Maria; Ali, Namra Amjad (Journal of Islamic Thought and Civilization, 2026)
Religious tourism has emerged as a vital driver of socio-economic development, cultural preservation, and sustainable growth in many regions. Among its diverse forms, Gurdwara Darbar Sahib at Kartarpur, one of Sikhs’ holiest places globally, has evolved as a popular religious tourism destination in Pakistan. This study investigated the complex impact of Gurdwara Darbar Sahib-related religious tourism on the region’s long-term economic prosperity. Using qualitative interviews with local stakeholders, such as business owners, community leaders, and pilgrims, as well as policy analysis, the study investigated how pilgrimage-driven tourism contributes to job creation, infrastructure development, and cross-border cultural exchange. The study also sought to identify challenges, such as seasonality, limited local capacity, and geopolitical constraints that impact long-term sustainability. The findings contribute to a deeper understanding of how well-managed religious heritage sites can serve as catalysts for inclusive development, cultural diplomacy, and regional economic revitalization, sustainable development, and cultural resilience in contemporary tourism landscapes.